Literatura kuge v pandemični dobi - Komel, Mirt (Teorija in praksa, 2022)
The article deals with the issue of the plague found in a selection of literature: plague in the Greek camp from the first canto of Homer’s Iliad; the introduction to Boccaccio’s Decameron; Camus’ novel The Plague. Attention is paid to the causes of the plague and ways of doing away with it, which naturally change according to the literary means of expression (poetry, prose, novel) and the historical context (polytheism of antiquity, medieval monotheism, modern atheism). At the end, an interpretation of the current pandemic is provided.
Keywords: Boccaccio, Giovanni; Camus, Albert; Dekameron; epidemije; Homer; Iliada; infekcijske bolezni; Književnost; kuga; literarna interpretacija; Pandemije